2021
DOI: 10.5535/arm.20111
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Length of Stay in the Intensive Care Unit and Sarcopenia Among Hemiplegic Stroke Patients

Abstract: Objective To discuss the association between the length of stay at the intensive care unit (ICU) and sarcopenia among hemiplegic stroke patients. Methods This study evaluated 66 hemiplegic stroke patients with history of ICU admission using handgrip strength and bioelectrical impedance analysis to obtain height-adjusted appendicular skeletal muscle mass. The diagnosis of sarcopenia was made according to the muscle mass based on the Asian Working Group for Sarcopenia. The patients were divided into sarcopenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…A meta-analysis of 15 studies demonstrated a mean difference of 4.54 days (95% CI 2.49–6.59 days) in sarcopenic gastrointestinal oncological patients undergoing surgery, compared to non-sarcopenic ones [ 15 ]. A positive association of sarcopenia and prolonged LOS was also demonstrated in hemiplegic stroke patients (>60 years) in a study that applied the Asian Consensus for sarcopenia diagnosis [ n = 66; OR 1.19 (95% CI 1.02–1.38)] [ 28 ], and in hospitalized older adults with heart failure [ n = 64,476; OR 1.40 (95% CI 1.37–1.43)] [ 29 ]. In the current study, sarcopenia was not an independent predictor of prolonged hospital stay, and the short hospital stay of patients in our sample could justify it.…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis of 15 studies demonstrated a mean difference of 4.54 days (95% CI 2.49–6.59 days) in sarcopenic gastrointestinal oncological patients undergoing surgery, compared to non-sarcopenic ones [ 15 ]. A positive association of sarcopenia and prolonged LOS was also demonstrated in hemiplegic stroke patients (>60 years) in a study that applied the Asian Consensus for sarcopenia diagnosis [ n = 66; OR 1.19 (95% CI 1.02–1.38)] [ 28 ], and in hospitalized older adults with heart failure [ n = 64,476; OR 1.40 (95% CI 1.37–1.43)] [ 29 ]. In the current study, sarcopenia was not an independent predictor of prolonged hospital stay, and the short hospital stay of patients in our sample could justify it.…”
Section: Discussionmentioning
confidence: 98%
“…Prolonged immobilization affects the musculoskeletal system [ 25 ]. Muscle atrophy and weakness occur within 2 weeks after bed rest and are primarily observed in the lower limbs and antigravity extensors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier identification of sarcopenia will be helpful in reducing the risk of malnutrition, and earlier intervention for sarcopenia had been demonstrated to result in less disability, decreased duration of care, and reduced mortality at 1 year (14). Therefore, early identification of SRS is critical to the prevention of these complications, initiation of earlier intervention, and acceleration of recovery (15).…”
Section: Introductionmentioning
confidence: 99%